2g-2=8/2g-3

Simple and best practice solution for 2g-2=8/2g-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g-2=8/2g-3 equation:



2g-2=8/2g-3
We move all terms to the left:
2g-2-(8/2g-3)=0
Domain of the equation: 2g-3)!=0
g∈R
We get rid of parentheses
2g-8/2g+3-2=0
We multiply all the terms by the denominator
2g*2g+3*2g-2*2g-8=0
Wy multiply elements
4g^2+6g-4g-8=0
We add all the numbers together, and all the variables
4g^2+2g-8=0
a = 4; b = 2; c = -8;
Δ = b2-4ac
Δ = 22-4·4·(-8)
Δ = 132
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{132}=\sqrt{4*33}=\sqrt{4}*\sqrt{33}=2\sqrt{33}$
$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-2\sqrt{33}}{2*4}=\frac{-2-2\sqrt{33}}{8} $
$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+2\sqrt{33}}{2*4}=\frac{-2+2\sqrt{33}}{8} $

See similar equations:

| x-13/3=-6 | | .3t+1.4=4.2-0.1t | | 4.9t^2+10t=3.5 | | 2z-30=2(z-15) | | 10+7m=3(2m+5)+m | | 9x-8x=-9 | | (1/2x)+7=(3/4x)-4 | | (5^k)^3=(^3÷5)^3 | | a•164363-10=10 | | -20-3p=10 | | x-17/11=-2 | | 6-2(x+6)=3x+4= | | 5x+2=12x+19 | | 16x—192=9 | | 2x+5=23=5x | | -8+3k=7 | | 0.75x+0.05(2-x)=0.10(-11) | | 7-(16/x)=-1 | | x/4-4=3x/4-66 | | k-(-38)=32 | | 5x+7−2x=x−11 | | 9(2+x)=-54 | | 4(n-8)=2(2n+3)-38 | | 6x=-4(3-2x)=5(x-4)-10 | | -30=x+19 | | 2(y+2)-5=3(y+1) | | 2x+3+3x+1=x+12 | | -4(2a-14)=-8a+14 | | (x-3)(x+2)=126^2 | | 3x(5x-9)=7-4(x+1) | | x/3-x+2/7=2 | | s^2+5s-3=0 |

Equations solver categories